Homozygosity in the ApoE 4 polymorphism is associated with dysphagic symptoms in older adults. Issue 1 (22nd November 2013) - Mentz, H.; Horan, M.; Payton, A.; Ollier, W.; Pendleton, N.; Hamdy, S.
Summary Apolipoprotein E (ApoE) is the most well‐described genetic risk factor for Alzheimer's disease and nonpathological cognitive decline. While possession of the E2 allele may have protective properties, substantial research evidence suggests the E4 allele increases the risk of cognitive degeneration. As neurodegenerative processes are implicated in swallowing dysfunction, we hypothesized that the presence of ApoE 4 would be predictive of dysphagia symptoms in older adults. Eight hundred members of a genetically well characterized community dwelling elderly cohort received the Sydney oropharyngeal dysphagia questionnaire via mail. Cognitive function was also measured using the modified Telephone Interview of Cognitive Status (TiCS‐m) and depression with the Geriatric Depression Score (GDS). ApoE allele was genotyped on blood samples from all subjects and data analyzed using standard statistical software (SPSS version 16). Completed questionnaire response rate was 79% (23.5% men, 76.5% women; mean age 81 ± 5 years; range 69–98 years). Possession of one or more of the ApoE 4 and 2 alleles was found in 23.5% and 16%, respectively. Swallowing score was significantly related to GDS (rho 0.133, P < 0.001**) and age (rho 0.107, P < 0.007**) but not general cognitive function as measured by TICS‐m. Self‐reported swallowing function was not significantly associated with heterozygosity of any allele or homozygosity for E2 or E3 alleles. Although infrequent (1.1% of all subjects) ApoE E4 homozygosity was significantly associated with higher swallowing scores compared to all other allele combinations (P = 0.033) and while attenuated, was still predicted in multivariate regression modeling (B = 0.812; SE = 0.323; P = 0.012). We report the association between ApoE 4 homozygous genotype and self‐reported oropharyngeal dysphagia symptoms in community‐dwelling older adults. As this association is weakened by the multivariate analysis and the population frequency of ApoE 4 allele homozygosity is low, this finding while intriguing requires replication in larger independent cohorts.